Pembangunan Perikanan Skala Kecil Melalui Pendekatan Mata Pencaharian Berkelanjutan - Belvi Vatria (Politeknik Negeri Pontianak, 2021)
Since ancient times, small-scale fishing communities have always attracted attention to study because small-scale fisheries have an important role in human well-being and sustainable development. To ensure the sustainability of small-scale fisheries, the development will be more effective if it focuses on strengthening livelihoods. The purpose of this study was to conduct a literature review on small-scale fisheries development through a sustainable livelihood approach. This research method is literature study through descriptive analysis by regularly describing various data that has been obtained and then synthesized so as to produce clear and easy to understand understandings and concepts. The research found that the sustainable livelihoods approach should basically be understood as a tool or checklist for understanding poverty, how the government responds to the poor, and how the poor perceive their own poverty. The core concepts of the sustainable livelihoods approach are; people-centered, holistic, dynamic, building on strengths, macro-micro links, sustainability. This study also found that there are ten main ideas that represent a sustainable livelihood framework, namely; the context of vulnerability, livelihood assets, human capital, social capital, natural capital, physical capital, financial capital, the transformation of structures and processes, livelihood strategies, and livelihood outcomes.